Analyzing the content of the second primary grade mathematics book according to future thinking skills (Journal of the College of Basic Education, 2023)
The current research aims to know the percentage of future thinking skills in the content of mathematics textbooks for the second grade of primary school approved for teaching for the academic year (2021-2022), the researcher used the descriptive analytical approach method, and the research sample consisted of a second -grade mathematics book approved in the academic year (2021-2022), A content analysis tool was prepared for this purpose according to future thinking skills, and its validity was verified by presenting it to a number of experts, The idea unit (explicit and implicit), and (Holisti) adaptive reasoning and using frequency and percentages, and the research concluded that future thinking skills were all available atvarying proportion (very low-medium), so represented (46.55%), visualization (26.50%), problem solving (15.27%), and forecasting skills (15.27%). 11.68%), and respectively, and the researcher recommended the necessity of inviting specialists and those concerned with preparing school curricula for mathematics in the General Directorate of Curricula in the Ministry of Education to take advantage of the results that have been reached in working to achieve balance in including future thinking skills in the content of mathematics books for the primary stage, and suggested Conducting a similar study in other subjects and for different academic levels